ANALISIS FAKTOR YANG MEMPENGARUHI PERMINTAAN SUKUK RITEL SERI SR 05 - Isro’iyatu Mubarokah; Madjidainun Rahma (Nurul Jadid University, 2019)
The budget deficit financing instruments and government projects through sukuk have the potential to increase fiscal sustainability in the long run. Series Retail Government Sukuk which are state securities based on sharia principles issued by the Government as proof of the participation in Islamic Securities Assets, which are sold to individuals (ritail) or Indonesian citizens through a Selling Agent, with a minimum nominal amount determined also has increased nominal issuance since it was first published in 2009. The purpose of this study is to find out the factors that influence the demand for Retail Sukuk SR 05. The variables studied in this study are limited to the price of retail state sukuk, bank deposit interest rates, profit sharing ratio for bank deposits sharia, other bond prices and inflation rates. The form of this research is quantitative descriptive. The data used in this study are secondary data The analytical method used in this study is multiple linear regression analysis. The results showed that the factor that influenced the demand for SR 05 series sukuk was the price of the sukuk itself.